The Mela Study: exploring barriers to diabetes research in black and minority ethnic groups. Issue 1 (11th February 2014) - Hood, Gillian A.; Chowdhury, Tahseen A.; Griffiths, Christopher J.; Hood, Rosie K.E.; Mathews, Christopher; Hitman, Graham A.
Abstract : Background: Black and minority ethnic (BME) groups are particularly susceptible to diabetes and its vascular complications in the United Kingdom and most western societies. To understand potential predisposition and tailor treatments accordingly, there is a real need to engage these groups in diabetes research. Despite this, BME participation in research studies continues to remain low in most countries and this may be a contributory factor to reduced health outcomes and poorer quality of life in these groups. This study explores the barriers BME groups may have towards participation in diabetes research in one area of East London, and includes local recommendations on how to improve this for the future. Methods: A questionnaire designed from previously reported exploratory work and piloted in several BME localities was distributed at the East London Bangladeshi Mela and similar cultural and religious events in London, UK. People were asked opportunistically to complete the survey themselves if they understood English, or discuss their responses with an advocate. The purpose of the questionnaire was to understand current local awareness with regards to diabetes, identify specific BME barriers and attitudes towards diabetes research by ethnicity, gender and age, and gain insight into how these barriers may be addressed. Results: Of 1682 people surveyed (16–90 years; median age 40 years), 36.4% were South Asian, 25.9% White, and 11.1% Black and other ethnicities; 26.6% withheld their ethnicity. Over half cited language problems generally (54%) and lack of research awareness (56%) as main barriers to engaging in research. South Asian groups were more likely to cite research as too time consuming (42%) whereas Black groups were more concerned with potential drug side effects in research (39%). Participants expressed a general mistrust of research, and the need for researchers to be honest in their approach. Recommendations for increased participation in South Asian groups centred round both helping the community (61%) and improving health (55%). With regards to gender influences, females (34.6%) were significantly more likely to fear drug side effects than males (23.8%), P <0.001. Females were also significantly more likely not to participate in research due to fear of experimentation (25.8%) compared with males (18.9%) P= <0.001. Conclusion: Initial findings from the study demonstrate that in East London research barriers are focused on time, drug side effects, lack of awareness and language. There is a perception that research is time consuming even though the majority of those surveyed had not taken part in a research study. Further potential solutions from the survey have suggested that researchers also need to involve BME community leaders in their study strategy and indicate any individual health benefits to participation in research. Accessible studies with regards to time and advocacy provision need to be included in the design.